COPING UNDER OPPRESSION: A LAZARUS AND FOLKMAN ANALYSIS OF JIA’S PSYCHOLOGICAL SURVIVAL IN HYEJIN KIM’S JIA: A NOVEL OF NORTH KOREA - Manurung, Ontje (Conscientia - Journal on Language, Literature, and Culture, 2025)
This study examines the psychological survival of the protagonist in Jia: A Novel of North Korea by Hyejin Kim through the lens of Lazarus and Folkman’s stress and coping theory. The research aims to identify how Jia tolerates, minimizes, and adapts to the extreme sociopolitical pressures she faces as the daughter of a condemned political figure in a totalitarian regime. Employing a qualitative descriptive method, the study collects data through close reading of the novel—focusing on narration, character interactions, and depictions of surveillance, fear, and danger—supported by secondary sources on coping and psychological resilience. The analysis reveals that Jia consistently employs problem-focused coping through processes such as threat identification, planning, information gathering, evaluating alternatives, selecting viable solutions, and undertaking concrete actions to escape state control. These findings demonstrate that Jia’s strategies are not merely reactive behaviors but deliberate, adaptive responses shaped by continuous cognitive appraisal of risk. The study concludes that Lazarus and Folkman’s framework effectively illuminates how individuals under authoritarian oppression develop strategic psychological mechanisms to maintain agency, emotional stability, and the possibility of freedom. Keywords: coping, psychological survival, problem-focused